As organizações como sistemas políticos: uma leitura à luz do pensamento político de Hannah Arendt - Bustamante, Maria Teresa (2011)
The dichotomy between administration and politics has shown itself increasingly illusive due to the recognition, not only in academic studies but also in daily demonstration in public or private organizations, that both are inseparable, since they converse, interact and lead to make relevant and transcendental decisions to society. Besides this finding, there is a need to understand not only this relation between administration and politics but also, and especially, the organizational modern political agent in his human dimension. This analysis was based on the political thought of Hannah Arendt, considered one of the greatest thinkers of the twentieth century. The choice of the author aimed to make use of the critical potential of her ideas in an attempt to understand the political reality of contemporary life and the politics both present in and inherent in economic organizations. The study tried to demonstrate that the contribution of Arendt's political thought is fundamentally grounded in her concept of political, public, private and action realm, going through the concepts of authority, power, equality and speech, thus shaping the configuration of organizational space in which social relations are developed. In this organizational space, the political agent can reveal himself as a politically free and conscious man. However, it is worth pointing out that for this man to reveal himself politically free and conscious, he will need to overcome his own insecurities and contradictions, and owing to this, he will need to invest in his reflective capacity and "think about what he is doing" as Arendt teaches. According to the Arendtian concept of action, the organizational political agent also reveals himself by the initiative when starting something new (natality), by approaching others (plurality) and by means of the speech (the use of words), showing his identity. Based on Arendt's political thought, it could be argued that politics in its most human conception is inherent in man, and its practice feeds the most human of all the sensations, the pleasure of acting and interacting with others, intrinsic human activity of the organizational space reality. Finally, when analyzing the basic concepts of Hannah Arendt's political thought, it is possible to shape the conception of administration and politics as two interacting poles, corroborating the idea that both are linked and that the administrator's role is a political role. Thus, certain theories that address both conceptions separately and still do not recognize this political branch as a characteristic of the administrator should seek an approach that considers politics an entity belonging to administration.